2008
DOI: 10.1590/s0103-863x2008000200011
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de maus-tratos em crianças de 1ª a 4ª série da cidade de Ribeirão Preto-SP

Abstract: Resumo: O presente estudo buscou mensurar a prevalência de maus-tratos em crianças matriculadas de 1ª a 4ª série em escolas da rede pública e particular da cidade de Ribeirão Preto-SP, Brasil, a partir de informações do setor da educação. A investigação adotou uma abordagem descritiva, de caráter epidemiológico. O instrumento utilizado para a coleta de dados foi a Cartilha Epidemiológica, aplicada junto aos professores para obter informações sobre o número e as características de casos suspeitos de maus-tratos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
2
2
0
2
Order By: Relevance
“…Based on this study's results, we note that most of the interviewed professionals (73%) reported they had contact with or suspected child abuse over the course of their careers, confi rming the fi ndings of other Brazilian and international studies (Faleiros & Bazon, 2008;Tite, 1994;Vagostello et al, 2006). However, another considerable portion of teachers (30%) reported they never had such an experience, which is somewhat surprising, considering they have worked 11 years on average in education and have had contact with a large number of children.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Based on this study's results, we note that most of the interviewed professionals (73%) reported they had contact with or suspected child abuse over the course of their careers, confi rming the fi ndings of other Brazilian and international studies (Faleiros & Bazon, 2008;Tite, 1994;Vagostello et al, 2006). However, another considerable portion of teachers (30%) reported they never had such an experience, which is somewhat surprising, considering they have worked 11 years on average in education and have had contact with a large number of children.…”
Section: Discussionsupporting
confidence: 81%
“…Taking into account the participants who reported having already suspected child abuse (more than two thirds of the total), the subsequent questions refer to the act of reporting or not reporting suspected or actually confi rmed cases of child abuse. In general, data show that the action of reporting is rare, corroborating the literature in the fi eld showing the severe problem of underreporting in this context (Faleiros & Bazon, 2008). The procedure most frequently adopted to deal with suspected cases, according to information provided, is try to solve the situation within the school context, without reporting.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Assim, verifica-se uma dupla dinâmica: com o crescimento/desenvolvimento da criança, e o incremento dos desafios colocados pelo seu comportamento, os responsáveis passariam a exercer um controle mais coercitivo sobre sua conduta, caracterizado por ameaças e/ou pela punição corporal, e/ou "abrindo mão" disso, desengajando-se ainda mais da tarefa de cuidar/educar (quando, então, verifica-se a "falta de controle parental") 55 . É certo que tanto a primeira quanto a segunda dinâmica, ou ambas, acontecendo concomitantemente, têm conseqüências negativas para o desenvolvimento físico e sócio-emocional da criança.…”
Section: Resultsunclassified
“…It is estimated that only 10% to 30% of cases are reported, showing the need to develop and improve interventions in the fi eld of family violence in Brazil (Bazon, 2008;Bérgamo, 2007;Faleiros & Bazon, 2008). Therefore, one of the main problems posed to the development of interventions involves the low rate at which cases of violence are identifi ed and then actually targeted in preventive actions, leading to an increased rate of violence, and consequently, to an increased number of fatalities (Conselho Nacional de Secretários de Saúde [CONASS], 2007).…”
Section: Validez De Criterio Del Inventario Child Abuse Potential (Cap)mentioning
confidence: 99%